Software Reading Techniques Twenty Techniques for More Effective Software Review and Inspection - Zhu, Yang‐Ming (Apress : Imprint: Apress, 2016)
This concise book teaches software professionals and software engineering students the full set of twenty software reading techniques to enhance their effectiveness in reviewing and inspecting software artifacts such as requirements specifications, designs, code files, and usability.  Software review and inspection is the best practice in software development whose purpose is to detect and fix problems early. Software professionals are trained to write software but not read and analyze software written by peers. As a result, individual reading skills vary widely. Because the effectiveness of software review and inspection is highly dependent on individual reading skills, differential outcomes among software readers vary by a factor of ten. Software Reading Techniques is designed to close that gap. Dr Yang‐Ming Zhu's depth of experience as a software architect, team leader, and scientist make him singularly well-equipped to bring software readers up to speed on all the techniques and tips for optimizing their effectiveness and efficiency, including the following: Software review and inspection procedures and reading skills Traditional and modern advanced reading techniques applicable to almost all software artifacts Specific reading techniques for software requirements specification, software design, and code.